The Historical Approach between Ibn Hishām and Ibn Saʿd in Sīrah Nabawiyyah - Mior Ahmad Ramdzan, Ummi Kamila; Azmi, Ahmad Sanusi (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
Sīrah Nabawiyyah has been the most widely used name for the traditional account of life and background of Prophet Muḥammad (PBUH). In the period of ninth century, Islamic literatures and biographies of the Prophet Muḥammad (PBUH) were actively developed as a reflection on the needs of Muslim community. Among the famous of the extant texts composed in the medieval Islamic genre is Sīrah Nabawiyyah by Ibn Hishām (d. 218/833 or 213/828) who rests mainly on his selection from the work of Ibn Isḥāq, and Kitāb al-Ṭabaqāt al-Kubrā by Ibn Saʿd (d.230/845) who compiled it from the works of his predecessors, specially al-Wāqidī and al-Kalbī. There are some studies conducted by Muslim and western scholars on the background of Ibn Hishām and Ibn Saʿd‘s works, however, the differences in the approach of writing Sīrah Nabawiyyah between them are hardly found. Thus, the present study aims to explore the style or pattern of historical approach applied by these two scholars on the biography of the Prophet Muḥammad (PBUH). The study is qualitative in nature, in which the researcher employed descriptive, comparative and source-critical approaches where it analyses and extract the approach used by the authors in writing Sīrah Nabawiyyah. The study in its finding infers that there are two opposing patterns of historical approach employed by Ibn Hishām and Ibn Saʿd in writing Sīrah Nabawiyyah.